(3GdeMjW GdHQgGfi aj Gdabg GdfYeGfis - (3eMehO Hf CMeO Hf YHO GdYRjR Hf YeQ Hf eGRg, HQgGf GdOjf, GdeQZjfGfj , J (B616 (3g` s ((3GdSjO Ndjd Hf GdSjO eMeO GdYHGS s)
(3ChdgG (B:s
(3GdYHO Ch GdLGQjI ai jO GdHGFY s
(3BNQgG (B:s
(3bHdJ TgGOJgeG ShGA TgOG HOjf bdjd Ch cKjQ hGddg CYde HGdUhGH s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B147s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1619s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs